Synthesis of 3D-MoO2 microsphere supported MoSe2 as an efficient electrocatalyst for hydrogen evolution reaction. (23rd October 2017) - Luo, Jiaxian; Xu, Peiman; Zhang, Dawei; Wei, Licheng; Zhou, Dan; Xu, Weiming; Li, Jingwei; Yuan, Dingsheng
Abstract: Many efforts have been devoted to the exploration of non-noble-metal electrocatalysts for the hydrogen evolution reaction (HER) in recent years. Here, we have developed a 3D-MoO2 microsphere supported MoSe2 for HER, via a facile hydrothermal approach followed by selenylation treatment. Loosely stacked MoSe2 layers are formed on the conductive MoO2 surface, and act as active sites for HER. Meanwhile, the metallic inner MoO2 facilitates electron transport for proton reduction. In addition, the MoSe2 could protect the inner MoO2 from the acidic electrolyte in the HER precess. Significantly, the as-synthesized MoO2 /MoSe2 exhibits excellent catalytic activity for HER, characterised by a low onset potential of −101 mV vs reversible hydrogen electrode, a small overpotential of 167 mV at a current density of 10 mA cm −2, along with Tafel slope values of 68 mV dec −1, as well as outstanding stability in 0.5 mol L −1 H2 SO4 .